Teacher's Strategy Using Environmental Media as a Learning Source in Improving Critical Thinking of Elementary School Students - Nurdiansyah, Deni; Agustin, Mubiar (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research departs from the declining tendency of critical thinking in elementary school students. Starting from the problem of limited media and children's learning resources, teachers use various materials in the surrounding environment as media and sources for the continuity of teaching and learning activities. The purpose of this study is to uncover the teacher's strategy of using environmental media in improving critical thinking of elementary school students. The approach used in the research is quantitative with survey methods related to the use of the surrounding environment as a source of learning and critical thinking skills. Research data obtained online using google form media. In this study, the number of respondents who became the sample in this study were 219 elementary school teachers spread across the West Bandung Regency area. The instrument used in this research is a questionnaire regarding the area of using environmental media as a learning resource and critical thinking area. The results showed that the application of critical thinking to students has often been done by teachers through environmental media as a learning resource with an average score of 41.9%. In addition, the research indicates that there are some teachers who have never developed critical thinking towards their students with a percentage of 1.69%. This makes it necessary to carry out alternative activities as an improvement effort through the teacher's strategy of using environmental media as a learning resource in improving critical thinking of elementary school students.